Le catalogue comme architecture en trompe-l’oeil? Les métamorphoses de la croix chez Tertullien et Minucius Felix - Fabien NOBILIO (Diversitate si Identitate Culturala in Europa)
In the first half of the 2nd Century C.E., Latin Apologists Tertullian and Minucius Felix wrote short catalogues of various things in which the shape of the Cross can allegedly be discovered. Both excerpts seem to complement each other in building an architecture not of knowledge but of belief and ritual process. Now this rhetoric building can be compared to an architecture in trompe-l’oeil style. This style might not only be due to the fancy of Christian writers, nor to the polemics with the Polytheists, but would better be seen as a way of shaping the imagination. Modern philosopher Thomas Hobbes’s criticism of idolatry highlights this process as well as it shows how easily it could be started with a catalogue.